The good, the bad and the ugly of COVID-19 lockdown effects on wildlife conservation: Insights from the first European locked down country. (September 2020) - Manenti, Raoul; Mori, Emiliano; Di Canio, Viola; Mercurio, Silvia; Picone, Marco; Caffi, Mario; Brambilla, Mattia; Ficetola, Gentile Francesco; Rubolini, Diego
Abstract: The COVID-19 pandemic zoonosis has determined extensive lockdowns worldwide that provide an unprecedented opportunity to understand how large-scale shifts of human activities can impact wildlife. We addressed the impacts of the COVID-19 lockdown on wildlife in Italy, the first European country that performed a countrywide lockdown, and identified potentially beneficial and negative consequences for wildlife conservation and management. We combined a qualitative analysis of social media information with field data from multiple taxa, data from citizen science projects, and questionnaires addressed to managers of protected areas. Both social media information and field data suggest that a reduction of human disturbance allowed wildlife to exploit new habitats and increase daily activity. The field data confirmed some positive effects on wildlife conservation, such as an increase in species richness in temporarily less-disturbed habitats, a higher breeding success of an aerial insectivorous bird, and reduction of road-killing of both amphibians and reptiles. Despite some positive effects, our data also highlighted several negative impacts of the COVID-19 crisis on wildlife. The lower human disturbance linked to lockdown was in fact beneficial for invasive alien species. Results from questionnaires addressed to managers of protected areas highlighted that the COVID-19 lockdown interrupted actions for the control of invasive alien species, and hampered conservation activities targeting threatened taxa. Furthermore, the reduction of enforcement could cause a surge of illegal killing of wildlife. The COVID-19 crisis, besides having deep socio-economic impacts, might profoundly affect wildlife conservation, with potentially long-lasting effects. Highlights: Lockdowns following COVID-19 provide an unprecedented opportunity for conservation studies. We combined multiple tools to understand Italian lockdown's effects on wildlife. Wildlife exploited new habitats and increased daily activity and breeding success. Also some invasive alien species took advantage from the lockdown. Negative effects occurred on conservation actions and alien species eradications.